2009
DOI: 10.1637/8925-051309-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore Receptor IroN Is an Important Protective Antigen Against Salmonella Infection in Chickens

Abstract: In iron-limiting environments, Salmonella enterica serovar Enteritidis and Salmonella enterica serovar Typhimurium synthesize and secrete several types of siderophore to trap trivalent ferric ions; these bacteria then express siderophore receptors called iron-regulated outer membrane proteins (IROMPs). In this study, we experimentally reproduced iron-limiting environments using a divalent metal chelator. IroN, one of the IROMPs, was purified by affinity chromatography with an anti-IroN-MAb-immobilized column. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…1) consistent with previous studies that revealed siderophore receptors including IroN as promising vaccine antigens in other models [70][72]. Interestingly, siderophore receptors are induced by iron starvation and/or activation of the PhoPQ two component sensory system [73].…”
Section: Discussionsupporting
confidence: 89%
“…1) consistent with previous studies that revealed siderophore receptors including IroN as promising vaccine antigens in other models [70][72]. Interestingly, siderophore receptors are induced by iron starvation and/or activation of the PhoPQ two component sensory system [73].…”
Section: Discussionsupporting
confidence: 89%
“…Iron-regulated proteins have previously been shown to be important in vaccine formulations against Pasteurella and Salmonella [37], [38]. Thus, we evaluated if the GMMA process would allow the upregulation of iron-regulated proteins.…”
Section: Resultsmentioning
confidence: 99%
“…salmonicida, with different restriction enzymes sites and position of asbD in the cluster the total membrane protein fractions (Butterton et al 2000). Recently, some siderophore components were used as an important protective antigen target to produce vaccines against Salmonella infection in chickens, meningitis in human and infections caused by E. coli in cattle (Kaneshige et al 2009;Marsh et al 2007; Thornton et al 2009). In a previous study, it was shown that AsbD protein is necessary to siderophore biosynthesis in A. salmonicida and that it is crucial for the growth of this bacterium under iron-limited conditions (Najimi et al 2008).…”
Section: Resultsmentioning
confidence: 99%